Military tactical adaptive decision making during simulated military operational stress is influenced by personality, resilience, aerobic fitness, and neurocognitive function - Sekel, Nicole M.; Beckner, Meaghan E.; Conkright, William R.; LaGoy, Alice D.; Proessl, Felix; Lovalekar, Mita; Martin, Brian J.; Jabloner, Leslie R.; Beck, Alaska L.; Eagle, Shawn R.; Dretsch, Michael; Roma, Peter G.; et al. (Frontiers in Psychology, 2023)
Laboratory-based studies designed to mimic combat or military field training have consistently demonstrated deleterious effects on warfighter’s physical, cognitive, and emotional performance during simulated military operational stress (SMOS). Purpose: The present investigation sought to determine the impact of a 48-hour simulated military operational stress (SMOS) on military tactical adaptive decision making, and the influence of select psychological, physical performance, cognitive, and physiological outcome measures on decision making performance. Methods: Male (n=48, 26.2 ± 5.5 yrs., 177.7 ± 6.6 cm, 84.7 ± 14.1 kg.) subjects currently serving in the U.S. military were eligible to participate in this study. Eligible subjects completed a 96-hrs protocol that occurred over five consecutive days and four nights. Day 2 (D2) and day 3 (D3) consisted of 48-hrs of SMOS wherein sleep opportunity and caloric needs were reduced to 50%. Differences in SPEAR total block score from baseline to peak stress (D3 minus D1) were calculated to assess change in military tactical adaptive decision making and groups were stratified based on increase (high adaptors) or decrease (low adaptors) of the SPEAR change score. Results: Overall, military tactical decision-making declined 1.7% from D1 to D3 (p < 0.001). High adaptors reported significantly higher scores of aerobic capacity (p < 0.001)., self-report resilience (p = 0.020)., extroversion (p < 0.001)., and conscientiousness (p < 0.001). at baseline compared to low adaptors, while low adaptors reported greater scores in Neuroticism (p < 0.001). Conclusion: The present findings suggest that service members whose adaptive decision making abilities improved throughout SMOS (i.e., high adaptors) demonstrated better baseline psychological/self-reported resilience and aerobic capacity. Further, changes in adaptive decision-making were distinct from those of lower order cognitive functions throughout SMOS exposure. With the transition of future military conflicts placing higher priority on enhancing and sustaining cognitive readiness and resiliency, data presented here demonstrates the importance of measuring and categorizing baseline measures inherent to military personnel, in order to change and train one’s ability to suffer less of a decline during high stress conditions.